Analisis Transformasi Ekonomi di Provinsi Kalimantan Timur - Zhikry Fitrian (Jurnal Borneo Administrator, 2018)
East Kalimantan Provincial Regulation Number 7 Year 2014 concerning East Kalimantan Provincial Regional Plan (RPJMD) of 2013 – 2018 stipulates that the acceleration of economic transformastion is one of the East Kalimantan Province’s medium-term development strategies. The economic transformation is done to reduce the economic dependence of East Kalimantan Province on mining and quarrying sector by developing manufacturing sector of leading commodities. This study aims to find out whether the economic transformation in East Kalimantan Province has been implemented as proclaimed by East Kalimantan Provincial Government. Data analysis was conducted by calculating location quotient (LQ) index to find out which sectors are the economic base in East Kalimantan Province as well as shift-share analysis to identify whether economy structure transformation in East Kalimantan. LQ index calculation shows that mining and quarrying sector is the only base economic sector in East Kalimantan Province, while manufacturing sector has not become the economic base sector in East Kalimantan Province throughout 2010-2016. Meanwhile, result of the shift-share analysis shows that mining and quarrying sector remain the sector that sustains East Kalimantan Province economy throughout 2010-2016. Meanwhile the manufacturing sector still has slow economic growth and low competitiveness. This indicates that the economic transformation in East Kalimantan is still not running as proclaimed by the East Kalimantan Provincial Government. Keywords: economic transformation, manufacturing, mining and quarrying, location quotient, shift share. AbstrakPeraturan Daerah Provinsi Kalimantan Timur Nomor 7 Tahun 2014 tentang Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Provinsi Kalimantan Timur Tahun 2013-2018 menetapkan bahwa percepatan transformasi ekonomi merupakan salah satu strategi pembangunan jangka menengah Pemerintah Provinsi Kalimantan Timur. Transformasi ekonomi tersebut dilakukan untuk mengurangi ketergantungan perekonomian Provinsi Kalimantan Timur terhadap sektor pertambangan dan penggalian dengan cara meningkatkan sektor industri pengolahan komoditas unggulan. Kajian ini bertujuan untuk mengetahui apakah transformasi ekonomi di Provinsi Kalimantan Timur telah berjalan sebagaimana dicanangkan oleh Pemerintah Provinsi Kalimantan Timur. Analisis data dilakukan dengan menghitung indeks location quotient (LQ) untuk mengetahuisektor yang menjadi basis ekonomi di Provinsi Kalimantan Timur serta analisis shift share untuk mengetahuiperubahan struktur ekonomi Provinsi Kalimantan Timur. Perhitungan indeks LQ menunjukkan sektor pertambangan dan penggalian merupakan satu-satunya sektor basis di Provinsi Kalimantan Timur. Sedangkan sektor industri pengolahan belum menjadi sektor basis di Provinsi Kalimantan Timur pada periode 2010- 2016. Sementara itu, hasil analisis shift share menunjukkan sektor pertambangan dan penggalian merupakan sektor yang menopang perekonomian di Provinsi Kalimantan Timur sepanjang tahun 2010-2016. Sedangkan sektor industri pengolahan masih memiliki pertumbuhan ekonomi yang lamban dan berdaya saing rendah. Hal tersebut mengindikasikan bahwa transformasi ekonomi masih belum berjalan sesuai dengan yang dicanangkan oleh Pemerintah Provinsi Kalimantan Timur. Kata kunci: transformasi ekonomi, industri pengolahan, pertambangan dan penggalian, location quotient, shift share.